2018
DOI: 10.3390/ma11101811
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Low-Temperature Preparation of Plate-Like ZrB2-SiC Powders by a Molten-Salt and Microwave-Modified Boro/Carbothermal Reduction Method

Abstract: To address the various shortcomings of a high material cost, energy-intensive temperature conditions and ultra-low efficiency of the conventional boro/carbothermal reduction method for the industrial preparation of ZrB2-SiC powders, a novel molten-salt and microwave-modified boro/carbothermal reduction method (MSM-BCTR) was developed to synthesize ZrB2-SiC powders. As a result, phase pure ZrB2-SiC powders can be obtained by firing low-cost zircon (ZrSiO4), amorphous carbon (C), and boron carbide (B4C) at a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…It was worth noting that the synthesis conditions (1150 °C/60 min and 1200 °C/20 min) in the present work were considerably milder than in the cases of conventional BCTR (up to 1600 °C for several hours) using the identical type of reducing agent [12], and the molten-salt-solely-assisted BCTR (firing temperature of 1000 °C and dwelling time of 4 h) using even much more expensive magnesium (Mg) as a reducing agent [16]. These results demonstrated that the present MSM-BCTR method was promising for low-cost, energy-saving, and high-efficiency preparation of TiB 2 powders, which should be attributed to the combined effect of molten-salt medium and microwave heating, as described in the “Introduction” section and discussed in our previous papers [29,30].…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…It was worth noting that the synthesis conditions (1150 °C/60 min and 1200 °C/20 min) in the present work were considerably milder than in the cases of conventional BCTR (up to 1600 °C for several hours) using the identical type of reducing agent [12], and the molten-salt-solely-assisted BCTR (firing temperature of 1000 °C and dwelling time of 4 h) using even much more expensive magnesium (Mg) as a reducing agent [16]. These results demonstrated that the present MSM-BCTR method was promising for low-cost, energy-saving, and high-efficiency preparation of TiB 2 powders, which should be attributed to the combined effect of molten-salt medium and microwave heating, as described in the “Introduction” section and discussed in our previous papers [29,30].…”
Section: Resultsmentioning
confidence: 54%
“…B 4 C took part in the overall synthesis reaction (Reaction 1), as both boron source and reducing agent. To compensate for the volatilization loss of boron species at high temperature [30], the amount of B 4 C was slightly higher than the stoichiometric amount indicated by Reaction 1. To minimize the residual carbon in the final powder product, the stoichiometric amount of carbon was used in all the cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, 14)16) the reactant and salt medium would be evenly mixed and heated, and the target products could be formed in molten salt medium, which not only greatly reduces the synthesis temperature, but also greatly shortens the holding periods. For example, Zeng 17) et al prepared ZrB 2 SiC powders under a mild condition (1200°C/20 min) with ZrSiO 4 , B 4 C and amorphous carbon (C) as raw materials and NaClKCl as salt medium. Tian 18) et al synthesized tetragonal carbon nitride hollow tubes with excellent photocatalytic activity and adsorption properties by molten salt method at a temperature as low as 450°C.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods is the microwave-assisted carbothermal reduction, which is fast and cost-effective in synthesizing B x C nanomaterials, such as B 4 C boron carbide nanocrystalline powders [19,25] and carbon-rich BC 2 amorphous powders [26]. The carbothermal reduction technique has also been employed to synthesize metal nitrides [27], TiC powders [28], ZrB 2 powders [29], and TiB 2 powders [30]. Here, semiconducting boron carbon amorphous compounds with tunable bandgap were first synthesized using the microwaveassisted carbothermal reaction.…”
Section: Introductionmentioning
confidence: 99%